STRATEGI PEMERINTAH PADA OBJEK WISATA PANTAI PANANUARENG DESA TARIANG BARU KECAMATAN TABUKAN TENGAH DI MASA PANDEMI COVID-19 OLEH DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN KEPULAUAN SANGIHE - SAMAU, FERRY; RARES, JOYCE; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2021)
The purpose of this study was to find out the Government's strategy for the Pananuareng beach tourismobject, Sangihe Islands Regency during the pandemic Covid-19. This study uses a qualitative approach.Strategy can be seen from the 3 strategic indicators proposed by Fred R. David, namely StrategyFormulation, Implementation, Strategy Assessment. The strategy formulation carried out by the Cultureand Tourism Office of the Sangihe Islands Regency has been going well to formulate new plans and betterprograms for the future in developing the potential for the charm of Pananuareng Beach. Theimplementation of the implementation strategy carried out by the Sangihe Islands Regency Culture andTourism Office has been going well, the facilities and infrastructure are adequate and the existing resourcesare able to be mobilized properly, and also always urges visitors to always comply with health protocols. Wecan see from the strategic assessment of the formulation and implementation that the cultural and tourismservices have been going well.Keywords: Strategy, Government, Covid-19 Pandemic